A Case Report of Rhabdomyosarcoma of Uterine Cervix in a 7-Month-Old Child - Yasmin, Farzana; Ahmed, Md Ashraf Uddin; Begum, Tahmina; Ahmed, Tasnima; Baki, Md Abdul (BIRDEM Medical Journal, 2017)
Rhabdomyosarcoma is the soft tissue tumor derived from embryonic primary mesenchyme. Neck, head and genitourinary region are the common locations of rhabdomyosarcoma. Here, we report a 7-month-old child who presented with a protruding mass per vaginally. Abdominal examination revealed a 6 cm x 6 cm hard, irregular, non-tender mass at pelvic region. Ultrasound of abdomen showed large heterogenous pelvic mass of uterine origin. Magnetic resonance imaging of whole abdomen revealed an intrapelvic teratoma (9.5 x 7.4 x 10 cm3) with left sided hydronephrotic change as the mass was pressing the rectum and bladder. The child underwent a total hysterectomy. Histopathology result was suggestive of rahbdomyosarcoma of uterus. Birdem Med J 2017; 7(3): 242-244